Oncogenic potential of human pluripotent stem cell‐derived lung organoids with HER2 overexpression. Issue 8 (7th July 2021) - Miura, Akihiro; Yamada, Daisuke; Nakamura, Masahiro; Tomida, Shuta; Shimizu, Dai; Jiang, Yan; Takao, Tomoka; Yamamoto, Hiromasa; Suzawa, Ken; Shien, Kazuhiko; Yamane, Masaomi; Sakaguchi, Masakiyo; et al.
Abstract: Lung adenocarcinoma (LUAD) is the most common types among lung cancers generally arising from terminal airway and understanding of multistep carcinogenesis is crucial to develop novel therapeutic strategy for LUAD. Here we used human induced pluripotent stem cells (hiPSCs) to establish iHER2‐hiPSCs in which doxycycline induced the expression of the oncoprotein human epidermal growth factor receptor 2 (HER2)/ERBB2. Lung progenitors that differentiated from iHER2‐hiPSCs, which expressed NKX2‐1/TTF‐1 known as a lung lineage maker, were cocultured with human fetal fibroblast and formed human lung organoids (HLOs) comprising alveolar type 2‐like cells. HLOs that overexpressed HER2 transformed to tumor‐like structures similar to atypical adenomatous hyperplasia, which is known for lung precancerous lesion and upregulated the activities of oncogenic signaling cascades such as RAS/RAF/MAPK and PI3K/AKT/mTOR. The degree of morphological irregularity and proliferation capacity were significantly higher in HLOs from iHER2‐hiPSCs. Moreover, the transcriptome profile of the HLOs shifted from a normal lung tissue‐like state to one characteristic of clinical LUAD with HER2 amplification. Our results suggest that hiPSC‐derived HLOs may serve as a model to recapitulate the early tumorigenesis of LUAD and would provide new insights into the molecular basis of tumor initiation and progression. Abstract : What's new? Activation of human epidermal growth factor receptor 2 (HER2) likely contributes to the development of precancerous lesions that ultimately give rise to lung adenocarcinoma (LUAD). The mechanism driving HER2 activation in these tumors, however, remains uncertain. Here, HER2 overexpression in human pluripotent stem cell‐derived lung organoids (HLOs) induced the formation of tumor‐like structures, similar to those observed in adenomatous hyperplasia, and transformed the normal lung tissue‐like state of the HLO transcriptome to a state resembling clinical LUAD with HER2 amplification. This novel model for visualization of pre‐malignant transformation could greatly facilitate investigations into the molecular basis of tumor initiation.